2021
DOI: 10.1177/19433875211002049
|View full text |Cite
|
Sign up to set email alerts
|

Injuries of the Peripheral Mandibular Nerve, Evaluation of Interventions and Outcomes: A Systematic Review

Abstract: Trigeminal nerve injuries are common and there is currently no consensus on both timing and type of intervention to achieve the best outcomes. A systematic review was performed to compare the outcomes of the many different types of therapeutic interventions for nerve injury. PubMed, EBSCO, and Cochrane Review databases were used to search for studies published from January 1, 2000 to December 31, 2019. Included studies detailed treatment of an injury to peripheral branches of the trigeminal nerve, either known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…These facts suggest nerve repair is sophisticated and needs a long time 34 . Some researchers recommended surgery when neurosensory deficits showed no improvement 90 days post‐diagnosis 30 . Our study suggested that the significantly positive effect of CGF and laser treatments can be an alternative to surgery to some degree.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…These facts suggest nerve repair is sophisticated and needs a long time 34 . Some researchers recommended surgery when neurosensory deficits showed no improvement 90 days post‐diagnosis 30 . Our study suggested that the significantly positive effect of CGF and laser treatments can be an alternative to surgery to some degree.…”
Section: Discussionmentioning
confidence: 69%
“…; it has been widely used in the clinic and has achieved certain curative effect, but the efficacy is not good for patients with severe nerve damage. 29,30 CGF is a kind of gel extracted from patients' venous blood, which is rich in various growth factors. The technology for CGF clinical application is mature, so it is widely used in alveolar surgery and implant surgery which need soft and hard tissue increment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury to the IAN and LN during and after MTM surgery can have a variety of causes, including direct trauma to the nerve from rotating instruments during ostectomy or separation, sharp transection during flap preparation, or more indirect damage from compression or chemical disturbance from a hematoma or injection of local anesthetics [ 28 , 29 , 30 , 31 ]. Apart from complete transection of a nerve, which is usually noticed immediately during surgery, it is often difficult to determine the exact cause of nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…In symptomatic patients who do not show signs of improvement over time, surgical exploration and, if needed, intervention must be discussed. The overall outcome, as measured by functional sensory recovery, is acceptable, and quality of life can often be increased [ 31 ]. While some authors recommend waiting 90 days for spontaneous healing, recent research suggests improved outcomes after early intervention [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%